Solve the equation. -7 = h/5

Question

Asked 6/27/2016 8:17:36 AM

Updated 6/28/2016 4:41:06 AM

1 Answer/Comment

Flagged by Venen [6/28/2016 4:40:34 AM]

s

Question

Asked 6/27/2016 8:17:36 AM

Updated 6/28/2016 4:41:06 AM

1 Answer/Comment

Flagged by Venen [6/28/2016 4:40:34 AM]

Rating

8

-7 = h/5

h = -7*5

h = -35

h = -7*5

h = -35

Added 6/28/2016 4:41:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/28/2016 5:01:43 AM]

What is the solution of the equation?
3 = b + 3
A. 9
B. 6
C. 1
D. 0

Question

Updated 6/27/2016 9:11:23 AM

2 Answers/Comments

3 = b + 3

b + 3 = 3

b = 3 - 3

b = 0

b + 3 = 3

b = 3 - 3

b = 0

Added 6/27/2016 9:11:23 AM

This answer has been confirmed as correct and helpful.

What is the solution of the equation?
3 = b + 3
A. 9
B. 6
C. 1
D. 0
**Weegy:** 3 = b + 3
b + 3 = 3
b = 3 - 3
b = 0 (More)

Question

Expert Answered

Updated 6/27/2016 10:04:20 AM

0 Answers/Comments

-7 = h/5 User: -7 = h/5

Question

Updated 6/27/2016 1:29:58 PM

1 Answer/Comment

-7 = h/5

1/5h = - 7

5 * (1/5h) = (5)*(-7)

h= - 35

1/5h = - 7

5 * (1/5h) = (5)*(-7)

h= - 35

Added 6/27/2016 1:29:55 PM

This answer has been confirmed as correct and helpful.

-7=h/5
A. -7/5
B. 35
C. 12
D. -35
**Weegy:** -7 = h/5; h = -7 * 5; h = -35 (More)

Question

Updated 6/27/2016 1:35:01 PM

0 Answers/Comments

3p - 1 = 5(p - 1) - 2(7 - 2p)
A. 3
B. 0
C. -9
D. -10
**Weegy:** 3p - 1 = 5(p - 1) - 2(7 - 2p) 3p - 1 = 5p - 5 - 14 + 4p; 3p - 1 = 9p - 19; 9p - 3p = -1 + 19; 6p = 18; p = 18/6; p = 3 (More)

Question

Updated 6/27/2016 9:20:39 AM

0 Answers/Comments

33,131,033

questions answered

There are no comments.